“Cassava of the Indians”: narratives and memories of the relationships between humans and plants on the Oiapoque border (Amapá – Brazil): “Mandioca dos índios”: narrativas e memórias das relações inauguradas entre humanos e plantas na fronteira Oiapoque (Amapá – Brasil) (Revista de História da UEG (REVHIST), 2023)
The natural history of the Amazon is characterized as a center of independent domestication of plants, among them the cassava of the Indians (Manihot esculenta Crantz). Through the production of the ethnographic knowledge, combined to the bibliographical research on the subject, this article aim to discuss the process of domestication of the genus Manihot based on the narratives of different peoples originating from the current federative entity of Amapá/Brazil, the northern historical border that separates Brazil from the French overseas territory. The symmetrical dialogue with the original knowledge and narratives leads us to perceive the insufficiency of the conceptual framework proposed in domestication, which is not enough to delve into the issue of the appropriation of plants for human benefit. The oral narratives cited on in this article demonstrate a high level of complexity and chains of interrelationships that are not obvious to the Western scientific work, making it clear that the cultivation and development of different varieties of plants among indigenous peoples require other conceptual contributions not yet contemplated. Keywords: Manihot esculenta. Domestication of plants. Amazon amapaense.